Music, Circulation, and Poetry in the Songs of Pedro Ximénez Abrill Tirado - Izquierdo König, José Manuel (2019)
Since the rediscovery of the works of the Peruvian-Bolivian composer Pedro Ximénez Abrill Tirado, a growing interest in his work has developed. This is primarily due to his abundant output of instrumental, orchestral, and chamber music. Nevertheless, to this date his songs for voice and piano, totalling more than 200, have gone largely unnoticed; in particular, because they have been conserved in highly fragmented collections and with numerous duplications. In this article, we offer a classification of these songs from diverse sources and also a theoretical perspective for understanding them. We primarily propose a focus on the song as vehicle for circulation and expression of poetic texts from the period, above all from Spanish and American authors. Thus, the songs of Pedro Ximénez Abrill are not only a valuable repertory in their own right, but also a vehicle for exploring with greater attention the modes of circulation, reception, and appreciation of poetry and song in South America in the first half of the nineteenth century.